Beloved : [compact disc, unabridged] : a novel - Morrison, Toni (Random House Audio, 1998)
Staring unflinchingly into the abyss of slavery, this spellbinding novel transforms history into a story as powerful as Exodus and as intimate as a lullaby. Sethe, its protagonist, was born a slave and escaped to Ohio, but eighteen years later she is still not free. She has too many memories of Sweet Home, the beautiful farm where so many hideous things happened. And Sethe's new home is haunted by the ghost of her baby, who died nameless and whose tombstone is engraved with a single word: Beloved. Filled with bitter poetry and suspense as taut as a rope, Beloved is a towering achievement. After the Civil War ends, Sethe longingly recalls the two-year-old daughter whom she killed when threatened with recapture after escaping from slavery 18 years before.